Experiences of individuals with serious mental disorders in regular employment through the Individual Placement and Support model - Melián Cartaya, María Jesús; Arias Rodríguez, Ángeles; Rodríguez Pérez, Armando; Sánchez Suárez, María; Rodríguez-Novo, Natalia; Rodríguez-Novo, Yurena; Rodríguez Pulido, Francisco (Frontiers in Psychiatry, 2024)
This study shows the perspective, meaning and satisfaction perceived by people with Serious Mental Disorders during their experiences in regular employment. Methods: A mixed qualitative-quantitative methodology was used, applying semi-structured interview as qualitative information collection tool and the Indiana Job Satisfaction Scale as quantitative tool. The study period was from January 2021 to December 2022. A purposive sampling was performed with a sample of 24 people with Serious Mental Disorders who had obtained a job through an Individual Placement and Support (IPS) program during the study period. Semi-structured interview and the Indiana Job Satisfaction Scale were applied to this Serious Mental Disorder workers' sample. The Indiana Job Satisfaction Scale was also applied to a group of 24 workers without mental disorders in the same working conditions who served as control group.The results of the analyses of the Serious Mental Disorder workers' narratives show that perception of work experience is conditioned by individual, environmental and social predictors, as well as external factors as determining variables. Quantitative results obtained by the Indiana Job Satisfaction Scale reveal levels of job satisfaction resembling those of the rest of workers without Serious Mental Disorder. Discussion: These findings reinforce the significance of employment in the recovery process for individuals with Serious Mental Disorders and emphasize the importance of understanding the subjective meaning individuals attribute to their work experiences.